Successful national sailors exhibit better visual search strategies during a radio controlled simulated event - Walker, C.; Welman, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
The aim of the present research was to investigate the visual search strategies of South African sailors during a radio controlled stimulated race. Twenty-two sailors completed three radio controlled match races while wearing a mobile eye tracker (ASL Mobile Eye). Races lasted an average of 197.51 (s = 40.05) seconds. Assessed variables included the race performance, the search rate (total fixations, average fixation duration, frequency) and the percentage viewing time. Sailors were grouped according to professional sailing history rank, success rate in the simulation and their respective sailing classes. The results revealed that the top ranking group performed 13.9% fewer fixations per second compared to the bottom ranking group (p = 0.03). In terms of success rate, the successful group exhibited a more efficient visual search strategy consisting of fewer fixations (p = 0.01) of longer duration (p = 0.34). The dinghy class differs between the keelboat class (p = 0.02) and the multihull class in the percentage viewing time to the BOAT HULL location. This suggests that these sailors identified this location as a more valuable source of information.